2014
DOI: 10.1111/apt.12891
|View full text |Cite
|
Sign up to set email alerts
|

Relative adrenal insufficiency in chronic liver disease: its prevalence and effects on long‐term mortality

Abstract: SUMMARY BackgroundThe relationship between relative adrenal insufficiency (RAI) and chronic liver disease is unclear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
58
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(63 citation statements)
references
References 27 publications
5
58
0
Order By: Relevance
“…15,17,18 The CIRCI frequency of 20% identified in this study falls within the previously published range of similar studies. 13,14,[19][20][21] In line with previous study, 19 we found that CIRCI prevalence was tightly correlated with liver function as reflected by the CTP, MELD and AARC-ACLF scores. In addition, it was also dramatically elevated in ACLF patients at mid and late stages, compared to those at early stage.…”
Section: Discussionsupporting
confidence: 90%
“…15,17,18 The CIRCI frequency of 20% identified in this study falls within the previously published range of similar studies. 13,14,[19][20][21] In line with previous study, 19 we found that CIRCI prevalence was tightly correlated with liver function as reflected by the CTP, MELD and AARC-ACLF scores. In addition, it was also dramatically elevated in ACLF patients at mid and late stages, compared to those at early stage.…”
Section: Discussionsupporting
confidence: 90%
“…436 RAI has also been described in patients with cirrhosis and, although it is mainly present in critically ill patients with sepsis or septic shock (68.9%), it also affects non-critically ill cirrhotic patients (41.8%), including those with compensated cirrhosis. [437][438][439][440][441][442] The pathophysiology of RAI in cirrhosis is not well defined. Suppression of the hypothalamic-pituitaryadrenal axis activity, reduced effective volemia, which may impair adrenal perfusion, and both impaired cholesterol synthesis and enhanced pro-inflammatory cytokine production likely contribute to impair adrenal steroidogenesis.…”
Section: Relative Adrenal Insufficiencymentioning
confidence: 99%
“…They showed that AI prevalence in cirrhosis was 24%, and no AI in patients were found with chronic hepatitis. [ 18 ]…”
Section: Discussionmentioning
confidence: 99%